(untitled) (African Journal of Biomedical Research, 2023)
In this study the mode of action of Cinnamomum impressicostatum on Methicillin Resistant Staphylococcus aureus (MRSA) was evaluatewd. Cinnamon is one of the most popular spices used by mankind to enhance the flavour of his cuisine. In addition, cinnamon contains medicinally important essential oils in its leaves, stems, twigs, fruits and inner and outer bark. Many species of cinnamon are widely used in traditional medicinal systems around the world for the treatment of a wide variety of infectious diseases including tuberculosis and salmonellosis. The crude stem – bark water extract of C. impressicostatum was generated using sequential soxhlet extraction. The antibacterial activity of the extract was investigated by performing broth microdilution assays and determination of the Minimum Inhibitory Concentration (MIC). A time kill study was performed to determine the killing efficiency of the extract. Potential bacteriolytic activity of the extract against MRSA was evaluated. Potential summative or synergistic killing effects of the extract when supplemented with 7.5% NaCl was also determined. Leakage of intracellular cytoplasmic components through the bacterial plasma membrane was analysed by determining absorbance at 260 nm. Scanning Electron Microscopy was used to study the damaging effects of the extract on the cell wall of MRSA. The Soxhlet crude water extract of C. impressicostatum stem - bark recorded the highest zone of inhibition (i.e. 21.0  1.4 mm) in disk diffusion assays. Its Minimum Inhibitory Concentration (MIC) against MRSA was 19.5 g mL-1 and its Minimum Bactericidal Concentration was 39.0 g mL-1. The combinatorial effect of the extract supplemented with 7.5% NaCl resulted in a marked decrease in bacterial growth suggesting enhanced killing with the use of NaCl that may be summative or synergistic in nature. Evidence suggests that treatment with the crude extract causes cytoplasmic leakage, possibly by damage to the bacterial cell wall or cytoplasmic membrane. This was substantiated by post treatment scanning electron microscopic analysis which revealed alterations in cell wall topology, possible damage to the bacterial cell wall and plasma membrane and the presence of vast amounts of cellular debris. The results of this study indicate that the killing efficacy of C.impressicostatum stem - bark extract against MRSA is enhanced by NaCl and that treatment with the plant extract induces gross and irreversible cellular damage eventually leading to bacteriolysis. The bioactive compound(s) contained in the plant extract thus show immense potential for development into efficacious antibacterial drugs.